1.)
\\ \frac{8}{2} + \frac{1}{2} = \frac{9}{2} = > 5 - 3 \div \frac{9}{2} = \\ 5 - 3 \times \frac{2}{9} = \frac{45}{9} - \frac{5}{9} = \frac{40}{9} " alt="5 - \frac{3}{4 + \frac{1}{2} } = > \\ \frac{8}{2} + \frac{1}{2} = \frac{9}{2} = > 5 - 3 \div \frac{9}{2} = \\ 5 - 3 \times \frac{2}{9} = \frac{45}{9} - \frac{5}{9} = \frac{40}{9} " align="absmiddle" class="latex-formula">
2.)
\\ \frac{3}{3} - \frac{1}{3} = \frac{2}{3} = > \\ 3 + 4 \div \frac{2}{3} = 3 + 4 \times \frac{3}{2} = \frac{6}{2} + \frac{12}{2} = \frac{18}{2} = 9" alt="3 + \frac{4}{1 - \frac{1}{3} } = > \\ \frac{3}{3} - \frac{1}{3} = \frac{2}{3} = > \\ 3 + 4 \div \frac{2}{3} = 3 + 4 \times \frac{3}{2} = \frac{6}{2} + \frac{12}{2} = \frac{18}{2} = 9" align="absmiddle" class="latex-formula">
3.)
\\ \frac{6}{2} - \frac{1}{2 } = > \\ 6 - 5 \times \frac{2}{5} = \frac{30}{5} - \frac{10}{5} = \frac{20}{5} = 4" alt="6 - \frac{5}{3 - \frac{1}{2} } = > \\ \frac{6}{2} - \frac{1}{2 } = > \\ 6 - 5 \times \frac{2}{5} = \frac{30}{5} - \frac{10}{5} = \frac{20}{5} = 4" align="absmiddle" class="latex-formula">
4.)
\\ \frac{18}{3} + \frac{2}{3} = \frac{20}{3} = > \\ \frac{2}{5} + 4 \times \frac{3}{20} = \frac{2}{5} + \frac{3}{5} = 1" alt=" \frac{2}{5} + \frac{4}{6 + \frac{2}{3} } = > \\ \frac{18}{3} + \frac{2}{3} = \frac{20}{3} = > \\ \frac{2}{5} + 4 \times \frac{3}{20} = \frac{2}{5} + \frac{3}{5} = 1" align="absmiddle" class="latex-formula">
Тада!